A Human Long Non-coding RNA LncATV Promotes Virus Replication Through Restricting RIG-I–Mediated Innate Immunity - Fan, Jingjing; Cheng, Min; Chi, Xiaojing; Liu, Xiuying; Yang, Wei (Frontiers in Immunology, 2019)
Pattern recognition receptors sense pathogen components and initiate host antiviral innate immune responses, including inducing expression of interferons (IFNs). Long non-coding RNAs (lncRNAs) are emerging regulators of multiple biological processes. However, their roles in antiviral responses, especially through regulating the human innate immune system, are largely unexplored. Here, we characterized lncATV, a human-specific lncRNA, and found that it was up-regulated upon type I/III IFN stimulation and viral infection. LncATV was localized in the cytoplasm with relatively high expression in human monocytes, erythroleukemia cells, and hepatoma cells. Notably, lncATV knock-down significantly inhibited the replication of multiple RNA viruses, including hepatitis C, Zika, Newcastle disease, and Sendai viruses. Mechanistically, RIG-I antiviral signaling and IFN pathways were enhanced when lncATV expression was knocked down but were inhibited by overexpression of lncATV. RNA immunoprecipitation results demonstrated an association between LncATV and RIG-I. Collectively, our findings revealed the functional role of the novel, human-specific lncATV as a regulatory lncRNA restricting virus-associated innate immune responses.